Digital and innovative teaching in dermatology Practically oriented teaching online - Wittbecker, L. M.; Pham, C.; Wohlgemuth, L. K.; Hoang, M. A.; Bandholz, T. C.; Schuh, S.; Gihl, J.; Erfurt-Berge, Cornelia; Glaeser, R.; Welzel, J. (Die Dermatologie, 2022)
Background Due to the corona pandemic and also to the new competence-oriented catalogue of learning objectives in medicine and the master plan for medical studies 2020, the development of digital and practical teaching concepts has experienced a great increase in importance. Aim of the work As a result of this development, it was an important task to establish this combination and incorporate it into the curricular teaching process. Material and methods The "Toolkit dermatology" was established, which was sent to a total of more than 650 students at German university dermatology clinics. Using educational films, the students were able to practice their skills. In a further development, the toolkit was combined with classroom lectures and the students were asked to evaluate the toolkit online. Results The vast majority of students (95-100%) clearly stated that the toolkit helped them to develop their practical skills. Some of them were in fact motivated to complete a clinical traineeship/practical tertial year in dermatology (21-88%). The combination of toolkit and subsequent classroom teaching was also rated very positively (82.2%), as this hybrid mode of teaching provided a better understanding. Discussion Digital teaching formats as part of the concept of blended learning, i.e. the combination of virtual and analogue teaching formats, are becoming increasingly more important. Solutions for the disadvantages, such as the lack of real interaction and suitable examination formats, still remain to be found; however, the toolkit project demonstrates that hands-on and digital teaching can lead to high student motivation as well as a high educational standard.
CRIS-Team WoS Importer:2022-10-21